Utilization of MBD-MBS Questionnaire as a Screening Tool for Mouth Breathing Habits in Children 6-12 Years Old in Bandung, Indonesia - Sinta Sari Ratunanda; Retno Arun Winastuti; Lina Lasminingrum; Wijana Wijana; Farah Dayana Zahedi (Jurnal Respirasi, 2026)
Introduction: Mouth breathing is one of the earliest manifestations of obstructive sleep apnea (OSA). Despite the availability of validated screening tools for early detection, their use remains limited in Bandung, Indonesia. This study examined the use of the mouth breathing in the daytime-mouth breathing during sleep (MBD-MBS) questionnaire to identify mouth-breathing patterns and quantify OSA risk among children in Bandung, Indonesia. Methods: This cross-sectional study included 400 children in Bandung, Indonesia. Ethical approval was obtained before data collection. Based on responses to the MBD-MBS and Pediatric Sleep Questionnaire (PSQ), children were classified as complete nose breathers (CNB), complete mouth breathers (CMB), or partial mouth breathers (PMB). The prevalence of OSA and mouth-breathing patterns, and their associations, were analyzed. Results: Complete mouth breathers was the most prevalent mouth-breathing pattern (40.75%), particularly among children aged 6-9 years old. Moreover, OSA was more common in mouth breathers (CMB: 55.21%; PMB: 71.84%) than nose breathers (5.97%), with PMB showing the strongest association (71.8% screening positive). Conclusion: Using the MDB-MBS questionnaire, mouth breathing was identified as a strong predictor of OSA in children, supporting its utility as a practical and effective tool for early screening.